Pengembangan Modul Berbasis Problem Based Learning (PBL) untuk Meningkatkan Kemampuan Berpikir Kritis Siswa pada Materi Sistem Pernapasan Manusia di SMA Negeri 2 Percut Sei Tuan - Permata Sari, Nabila Syahna; Widya Ulfa, Syarifah; Nina Adlini, Miza (IAI Nasional Laa Roiba Bogor, 2025)
The Problem-Based Learning (PBL) module is a module characterized by problem-oriented learning that provides students with direct experiences, making the learning process student-centered. Critical thinking can be defined as the process and ability to understand concepts, apply, synthesize, and evaluate obtained or generated information. This study aims to investigate the development of a Problem-Based Learning (PBL) module to improve students’ critical thinking skills on the topic of the human respiratory system. The research technique used in this study is Research and Development (R&D), employing the 4-D model (Define, Design, Develop, and Disseminate), which is one of the research and development methods in the field of education. The research sample consisted of 36 students from class XI-A of SMA Negeri 2 Percut Sei Tuan. The instrument used in this study was a critical thinking skills test in the form of 10 pretest and posttest essay questions, based on critical thinking indicators. The results showed that the development of the Problem-Based Learning (PBL) module improved students’ critical thinking skills on the human respiratory system, with an N-Gain score of 0.77, categorized as high (effective). The pretest results were 39.44%, while the posttest results reached 95.55%.